2020
DOI: 10.3389/fphys.2020.00560
|View full text |Cite
|
Sign up to set email alerts
|

NBCe2 (Slc4a5) Is Expressed in the Renal Connecting Tubules and Cortical Collecting Ducts and Mediates Base Extrusion

Abstract: Arterial hypertension, is a common disorder with multiple and variable etiologies. Single nucleotide polymorphism analyses have detected an association between variants in the gene encoding the electrogenic Na + :HCO 3 − cotransporter NBCe2 (Slc4a5), and salt-sensitive hypertension. Mice with genetic deletion of NBCe2 are hypertensive, and the cause of the blood pressure (BP) increase is believed to arise from a lack of renal NBCe2 function. The exact cellular expression of NBCe2 in the kidney tubular system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…The electrogenic Na/HCO 3 cotransporter NBCe1 (SLC4A4) is the founding member of this SLC4 subfamily and is highly expressed in the kidneys, digestive system, and brain. 8 NBCe2 (SLC4A5), another electrogenic NBC, is mainly found in the liver, testis, and spleen 9 ; its physiologic importance has been addressed in the kidney 10 and choroid plexus. 11 NBCn1 (SLC4A7), an electroneutral NBC, is plentiful not only in skeletal muscle and heart 12 but also in epithelia ( e.g.…”
mentioning
confidence: 99%
“…The electrogenic Na/HCO 3 cotransporter NBCe1 (SLC4A4) is the founding member of this SLC4 subfamily and is highly expressed in the kidneys, digestive system, and brain. 8 NBCe2 (SLC4A5), another electrogenic NBC, is mainly found in the liver, testis, and spleen 9 ; its physiologic importance has been addressed in the kidney 10 and choroid plexus. 11 NBCn1 (SLC4A7), an electroneutral NBC, is plentiful not only in skeletal muscle and heart 12 but also in epithelia ( e.g.…”
mentioning
confidence: 99%
“…In a population survey, it was found that people with hypertension have a higher risk of gallstones than the general population, which may be related to the mutation of SLC4A5 gene loci ( Song et al, 2020 ). A number of studies have pointed out that there is a genetic association between SLC4A5 gene polymorphism and hypertension ( Parker, 2018 ; Barbuskaite et al, 2020 ). A healthy diet can reduce the risk of gallstone disease while preventing high blood pressure ( Wirth et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A related function of MFAP5 is that it can remodel extracellular matrixes that may play a role in supporting hESC growth [ 19 ]. A protein that transports sodium and bicarbonate across the cell membrane as well as regulates cellular pH is encoded through SLC4A5 [ 20 ]. ADAMTS-4 is a metalloprotease that plays a role in aggrecan degradation in an extracellular matrix [ 21 ].…”
Section: Discussionmentioning
confidence: 99%